UTAUT: capturing differences in undergraduate versus postgraduate learning?. Issue 9 (10th October 2016) - McKeown, Tui; Anderson, Mary
Abstract : Purpose: While educators and students alike are increasingly moving to use on-line technologies, there is still much to be learned about how these tools influence student learning. The purpose of this paper is to present a comparative investigation of the online use of one undergraduate (UG) and two postgraduate (PG) student cohorts undertaking similar "introduction to management" courses. Design/methodology/approach: The authors used the Unified Theory of Acceptance and Use of Technology (UTAUT) framework to examine student cohorts' (UG vs PG, with two nuances within PG) use of the same online learning platform. Findings: Students' acceptance and use of technology increases as the authors move from UG to PG with little to no work experience and were highest for PG students with two years plus work experience. These findings suggest that educators delivery of materials via online learning platforms requires a more nuanced approach than the "one-size fits all" that tends to be adopted. Research limitations/implications: The study is confined to students undertaking management in the academic rather than vocational area and the authors have limited the study to a quantitative methodology which uses regression analysis. Practical implications: This current study provides academic practitioners with an insight into some of the challenges facing higher education in managing different student cohorts in ways that provide them all with what is seen as a quality learning experience. Originality/value: Given the relatively recent development of the UTAUT model, the authors suggest that an important part of its value is in providing comparative UG vs PG views as to the effectiveness of online and technology-assisted learning tools.